Algoritma Dijkstra dan Algoritma Greedy Untuk Optimasi Rute Pengiriman Barang Pada Kantor Pos Gorontalo - Novria Fatmawati Lakutu; Sri Lestari Mahmud; Muhammad Rifai Katili; Nisky Imansyah Yahya (Universitas Negeri Gorontalo, 2023)
Delivery of goods is one of the services used in the online buying and selling process at the Post Office company. Companies need a performance in the distribution of goods that is more time-consuming and cost-efficient, so it requires determination in selecting the shortest path. Many algorithms have been used to help find the shortest path for distributing goods, including the Dijkstra Algorithm and the Greedy Algorithm. In this study, the application of the two algorithms is to find routes between sub-districts that are the destination of goods delivery, then compare to see which algorithm is more optimal. Based on the calculation results, the Dijkstra Algorithm can provide a more optimal solution with a total mileage obtained of 304.90 Km, while the Greedy Algorithm produces a total distance of 441.60 Km.